An Unfair Start - UNICEF Innocenti Research Centre (United Nations, 2019)
This report focuses on educational inequalities in 41 of the world’s richest countries, all of which are members of the Organisation for Economic Co-operation and Development (OECD) and/or the European Union (EU). Using the most recent data available, it examines inequalities across childhood – from access to preschool to expectations of post-secondary education - and explores in depth the relationships between educational inequality and factors such as parents’ occupations, migration background, the child’s gender and school characteristics. The key feature of the report is the league table, which summarizes the extent of educational inequalities at preschool, primary school and secondary school levels.